Evaluating Community Based Initiatives’ Sustainability in Europe: Balancing Data Needs and Resulting Uncertainties. - Martellozzo, Federico; Reusser, Dominik; Groß, Helge (European Journal of Sustainable Development, 2017)
Global environmental-change is evident, and undeniably it is mostly induced by anthropogenic activities. Several programs fuelling climate-change mitigation were lately implemented; all fostering specific and ambitious targets. Although some improvements were regionally observed, regrettably the expected results are in many cases still out of reach. Contemporaneously, societies experienced a proliferation of grass-roots initiatives calling for individual participation in fostering societal sustainable transition. Scholars advocate that bottom-up activities may outperform top-down policies in reaching sustainability; however, a methodological framework to intelligibly assess CBIs’ impact on socio-ecological systems is still unexplored. This paper aims at: illustrating main caveats in assessing CBIs’ environmental impacts, proposing a general methodological framework, presenting results from a pan-European research. Keywords: Environmental assessment; greenhouse gas emissions; community based intiatives; sustainable transition, sustainability, carbon footprint.